Enrichment of organic complex compounds of coconut water and mungbean extract in chrysanthemum (Chrysanthemum morfolium L.) tissue culture media. Issue 1 (April 2020) - Mollah, A; Kaimuddin,; Hamdi, E; Haring, F; Ulfa, F; Ridwan, I; Sarif, M
Abstract: A study was conducted aimed to determine the most effective concentration of mungbean sprouts extract and coconut water in chrysanthemum tissue culture to promote growth of chrysanthemum plantlet. The trial was conducted at the Tissue Culture Laboratory, Horticulture Seed Center, Bonto-Bonto District, Gowa Regency, South Sulawesi Province from August to December 2017 using a Randomized Block Design. Seven combination of Murashige and Skooge (MS) culture media added with mungbean sprouts extract and coconut water were used as treatments consisted of the addition of 1 ppm BAP synthetic hormone, coconut water (50, 75, and 100 ml/L, respectively) and mungbean sprout extract (20, 40, and 60 ml/L, respectively). The results show that the addition of coconut water and mungbean sprout extracts in the culture media had a significant effect on the parameters of time of shoots emergence, plantlet height, number of leaves, number of roots and root length. The addition of coconut water as much as 75 ml/L showed the best results based on the parameters of the time of shoots emergence. While the addition of mungbean sprout extract with a concentration of 40 ml/L showed the best results based on the parameters of plantlet height, number of leaves and root length.